Challenges Facing the Community in using Public Transport: A Case of Nkuhungu Ward in Dodoma City Council (Global Journal of Human-Social Science, 2020)
The study of assessing challenges facing the community in using public transport was conducted at Nkuhungu ward in Dodoma city council The objectives of this study was to assess challenges facing the community in using public transport to evaluate availability of commuter buses examine the challenges and determine possible measures Methodology of study applied qualitative and quantitative data collected from respondents were summarized coded be analyzed and entered using statistic package for social science SPSS computer software used descriptive statistics to obtained means frequencies percentages and cross tabulations were used to obtain relationships between variables The result reveals that the availability of commuter buses in Nkuhungu is good about 68 8 and 1 0 is bad Also challenges facing passengers in using commuter buses majority 17 71 addressed that bad communication is one of big challenge that community faces and minority 4 17 injuries as a challenge About 25 of respondent addressed education and training as a possible measure and 4 17 suggested building bus stop near the community The study recommended that the ministry of home affairs and Sumatra should review their laws and policy and enforce them Service providers must provide good customer care Dodoma city councilor Sumatra and other stakeholders should increase bus stop and construct bus stop near the community Training should be provided to the service providers and their crew by stakeholders and owners of the buses concern with how to provide service work ethics and owners of the buses they must provide full time employment to physical mental and health people
Keywords: community; transport and public